KINERJA KARYAWAN PT NOBI PUTRA ANGKASA DIPENGARUHI OLEH DISIPLIN KERJA MELALUI LINGKUNGAN KERJA - Adya Meivy Khanza; Eddy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This study aims to determine employee performance which is influenced by work discipline directly or indirectly through the work environment as an intervening variable at PT Nobi Putra Angkasa. The method used in this research is a quantitative approach method. Sampling technique using a census. Method of analysis using path analysis techniques The results showed that 1) Work discipline has a positive and significant effect on employee performance 2) Work environment has a positive and significant effect on employee performance 3) Work discipline has a positive and significant effect on work environment. 4) Employee performance is not influenced by work discipline through the work environment.